Pengaruh Kualitas Pelayanan Dan Kepuasaan Terhadap Loyalitas Konsumen Pada Puskesmas Bandar Jaya Lahat - Hasanah, Titi (MOTIVASI, 2020)
Purpose – In this study entitled "The Effect of Service Quality and Satisfaction on Consumer Loyalty at the Bandar Jaya Community Health Center, Lahat District, Lahat Regency", the authors examined whether there was a positive relationship between service quality and satisfaction with patient loyalty at Puskesmas Bandar Jaya Kacamatan Lahat district.The purpose of this study was to determine: the quality of employee services implemented in the Bandar Jaya Community Health Center, the patient's satisfaction with the loyalty of the Bandar Jaya Lahat Community Health Center, and the influence of service quality and patient satisfaction on consumer loyalty at the Bandar Jaya Lahat Community Health Center.Design/methodology – The method used in this research is descriptive and verification methods through a survey approach. The sampling method in this study is the incidental sampling method,  which is a sampling technique based on chance, that is, anyone who accidentally meets the researcher can be used as a sample, if it is considered that the person who happened to be met is suitable as a data source. The number of visitors who will become respondents is calculated using the Slovin formula. The number of respondents in this study with the largest error rate of 5% (confidence level (95%) is 100 respondents.Findings - Based on the results of the calculation of the spearman rank correlation, it was obtained rs of 0.766, meaning that the variable service quality (X1), satisfaction (X2) had a strong relationship with patient loyalty (Y) at the Bandar Jaya Lahat Community Health Center. The calculation of the coefficient of determination in percent yields a result of 58.6%, meaning that the variable service quality (X1) and satisfaction (X2) have an influence on patient loyalty, amounting to 58.6% and the remaining 41.4% is influenced by other factors. From the results of hypothesis testing, it is found that the value of F count (68,740)> F table (3,232) means that Ho is rejected and Hi is accepted. Thus, service quality (X1) and satisfaction (X2) have a positive effect on patient loyalty (Y) at Bandar Jaya Lahat Community Health Center.